SEJARAH PERKEMBANGAN PERUNDANG-UNDANGAN WAKAF DI INDONESIA - Heru Susanto (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Endowment practice in Indonesia has been accepted by the societies (customary law) since the first time of Islam comes to Archipelago. It is designated by the establishment of mosques being built on waqf land. Subsequent to Indonesia's liberty, the government issued several regulations regarding waqf, such as Government Regulation No. 28 of 1977 concerning Perwakafan Tanah Milik (Endowment of freehold estate), PMA No. 1 of 1978 concerning Implementing Regulation Government Regulation No. 28 of 1977 concerning waqf lands, Islamic Law Compilation (KHI), and other regulations. Devining to the enahncement of waqf law, it is necessary to review the historical overview deeply to recognize the development of waqf in the Indonesia